The Effect of Workload on Turnover Intention with Job Satisfaction as an Intervening Variable - Nurullita Aprillianti; Umar Mansur; Harini Fajar Ningrum (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2023)
This study has the aim of knowing how the impact of the workload of Turnover Intention with job satisfaction becomes an intervening variable at the Garment X employee department employees in Sukabumi. This type of research is quantitative with the survey method. By utilizing the Slovin formula, the number of samples was 94 of the 1602 populations. Research variable data is managed using SPSS 25. The data analysis technique used is the path analysis path (a development analysis technique of a double linear regression model), coefficient of determination (R²), hypothesis testing. The results of this study show that the workload has a positive and meaningful impact on turnover intention, the workload has a negative and significant effect on job satisfaction, job satisfaction has a negative impact and means to turnover intention, and the results of the path analysis show that job satisfaction can be intermediary variables of the workload of Turnover Intention. This means that the number of jobs delegated for employees can result in decreasing employee job satisfaction so that it will have an impact on the increasing desires of employees to leave their work.